(untitled) (REMUNOM, 2024)
The Brazilianhealth model emphasizeshealthpromotionandpreventivemeasures, as well as theOne Health approach, whichencompasseshealthissuesatthehuman-animal-environment interface. This includes multidisciplinaryknowledge in decision-making onpublichealthtopics. Since 2011, theinclusionofveterinarians in the Family Health Support Center (NASF) demonstratesrecognitionoftheirimportance in thiscontext, supporting Family Health Strategyteams. Veterinarians are professionalstrainedtoact in varioussituationsrelatedtohealthpromotion, zoonoticdiseaseprevention, andadvisingprofessionalswhodirectlydealwiththepreventionofaccidentsinvolvingvenomousanimals, amongmanyotherissuesthatcontributetotheOne Health perspective. Therefore, thisstudyaimedtospecifytheareaswhereveterinarianscanworkalongsideotherprofessionals in thepreventionofdiseasesandhealthpromotionwithin NASF. Verifyingwhetherthereisrecognitionfromthepopulationandhealthprofessionalsaboutthe roles veterinarianscan play in thispublichealthcontextis crucial for theappreciationoftheprofessionand its opportunities in thejobmarket. For thispurpose, a literature review wasconductedonthe role ofveterinariansthroughresearch in books, dissertations, andscientificarticlesrelatedtothistopic, published in thelast 10 years. It wasfoundthatalthoughveterinarians are recognized as essentialprofessionals in NASF, contributingtothecommunity’scomprehensivehealthandpromoting a One Health approach, theresultssuggestthatthere are still significantbarriersthatneedtobeovercome for effectivecollaborationbetweendifferenthealthsectors. Thereisalso a need for greaterinclusionofveterinarians in the NASF professional team. Keywords:veterinarian in publichealth; venomousanimals; zoonoses; dengue.